Otolith growth rings pattern in barau fish (Hampala macrolepidotaKhul & Van Hasselt, 1823) in the Teluk Petai Lake, Kampar Regency, Riau Province - Siahaan, Lamminar Juliaty; Efizon, Deni; Efawani, Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractThe Teluk Petai Lake is an oxbow lake that received water from the Kampar River. The lake, however, received domestic pollutant that negatively affects the water and thus affect the life of fishes, including Hampala macrolepidota living in that lake. To understand the growth ring pattern in the otolith of that fish, a study was conducted on November to December 2020. The fish was sampled using nets with 3/4 and 2,3 inch mesh size, 4 times, once/ week. The fish captured was then measured, weighed and the otolith (sagita) was removed. The otolith was then sticked in slide glasses using Crystalbond Amber 509 and then shaved manually using whetstone to reveal the growth ring patterns. The dark ring was identified using a binocular microscope. Results shown that among 50 fishes captured (200 – 350 mm TL, 90 – 320 gr BW), 48 fishes have dark growth rings, 1 – 3 rings/ fish. The distance between the otolith’s nucleus and the 1st growth ring was various, ranged from 0.1 – 0.75 mm, indicating that the formation the growth ring is individual and it is not resulted from mass evidence. Based on data obtained, it can be concluded that mostH. macrolepidota in the Teluk Petai Lake faced problems that hampered their growth as indicated by the formation of dark rings in the otolith.Keywords: Oxbow lake, Growth pattern, Sagita, Hampala barb